Acute pectoralis major tears in active duty US military personnel: Midterm outcomes of repairs performed in the forward-deployed setting. (28th May 2019) - Salazar, Dane; Davis, William; Shakir, Irshad; Joe, Keith; Choate, W Steven
Purpose: To report midterm outcomes of a series of acute pectoralis major tears repaired surgically in the deployed setting in active duty military personnel. Methods: Analysis of acute pectoralis major tears treated at one expeditionary medical treatment facility during a 4-month time frame. Results: Nine male patients with a mean age of 32 years (23–52) were diagnosed with tears; seven underwent operative fixation in the forward deployed setting. All injuries occurred during bench press, with the dominant upper extremity involved 56% of the time. With an average final follow-up of 4.1 years, the mean disabilities of the arm shoulder and hand score was 35.71 (range 31–41) and the mean American shoulder and elbow surgeons score was 90.71 (range 87–95). All personnel returned to their preinjury jobs with an average return to full preinjury function occurring at 7 months (range 4.5–10.5 months) in the operative group. Conclusions: Combat-deployed active duty US military personnel likely represent a high-risk population for this injury. Our study demonstrates that with at least 4 years of follow-up, surgical repair with a trough and trans-osseous repair technique was technically feasible and clinically successful in the deployed setting. Although this treatment may be considered in rare individual cases moving forward, due to the lengthy postoperative restrictions, inability to return back to duty in a timely manner, and lengthy rehabilitation, we no longer recommend this surgery be performed in theater.